Oxygen saturation among newborns in the first 10 hours of life to detect Critical Congenital Heart Disease - Ductus Dependent - Fatchul Wahab; Mahrus Abdul Rahman; Teddy Ontoseno; Risa Etika; Alit Utamayasa; Taufiq Hidayat; Sarmanu Sarmanu (Universitas Muhammadiyah Surabaya, 2020)
ABSTRACT Delay diagnosis of Critical Congenital Heart Disease (CHD) can be associated with sudden clinical deterioration and dangerous cardiovascular conditions. The oxygen saturation screening among newborns in the first 10 hours of life is essential for early detection of critical CHD. This study aims to prove that measuring oxygen saturation among newborns in the first 10 hours of life can detect critical CHD. This study is a diagnostic experimental with consecutive sampling subjects in the infant care unit of Dr. Soetomo Hospital, including all newborns with birth weight ≥ 1500 grams and oxygen saturation at ≥ 1 hour of age below 90%. The measurement of oxygen saturation uses fingertip pulse oximetry in the right hand and foot at the age of 10 hours. A